Cardiac birth defects caused by lifestyle and their potential prevention by nutritional molecules - Memon, Samreen (2010)
Congenital heart defects are responsible for more neonatal deaths than any other birth defect. Although genetic and environmental factors play an important role, either separately or in combination (multifactorial), still the cause in most cases remains unknown.